Alchemy of bones : Chicago's Luetgert murder case of 1897 - Loerzel, Robert, 1966- (Urbana ; Chicago : University of Illinois Press, 2003)
"On May 1, 1897, Louise Luetgert disappeared. Although no body was found, Chicago police arrested her husband, Adolph, the owner of a large sausage factory, and charged him with her murder. The eyes of the world were still on Chicago following the success of the World's Columbian Exposition, and the Luetgert case, with its missing victim, once-prosperous suspect, and all manner of gruesome theories regarding the disposal of the corpse, turned into one of the first media-fueled celebrity trials in American history." "Newspapers fought one another for scoops, people across the country claimed to have seen the missing woman alive, and each new clue led to fresh rounds of speculation about the crime. Meanwhile, sausage sales plummeted nationwide as rumors circulated that Luetgert had destroyed his wife's body in one of his factory's meat grinders." "In this narrative history of the Luetgert case, Robert Loerzel brings 1890s Chicago vividly back to life. He examines not only the trial itself but also the police department and forensic specialists investigating the case, the reporters scrambling for details, and the wider society who followed their stories so voraciously."--BOOK JACKET.
Introduction -- Omens -- Legends -- The englishman -- Everything is gone -- Moving day -- Missing -- Case histories -- The search -- Strong stuff -- Grewsome clews -- The sweating -- The woman in black -- Cell 21 -- Spring and summer -- Fixed opinions -- The rustling noise -- The morbid women -- Trained beasts -- Trial by newspaper -- The throwing mania -- The widow -- The experiments -- Cries and whispers -- The experts -- Autumn -- The kiss -- Sideshows -- A game of tag -- Just a plain domestic girl -- The many Mrs. Luetgerts -- Soap and bones -- Cigar talk -- Oratory -- Twelve men -- Queer reports -- Telescopic views -- Aftermath -- Editorials -- Between trials -- Turbulence -- The ghouls -- Denials -- Winter -- The verdict -- Lines of destiny -- Prisoner 5969 -- Confessions and eulogies -- Epilogue.
Includes bibliographical references and index.
JSTOR
Keywords: Luetgert, Adolph Louis, -- 1845-1899.; Luetgert, Adolph Louis, -- 1845-1899; Murder -- Illinois -- Chicago; Murder -- Investigation -- Illinois -- Chicago; Trials (Murder) -- Illinois -- Chicago; Meurtre -- Illinois -- Chicago; Meurtre -- Enquêtes -- Illinois -- Chicago; Procès (Meurtre) -- Illinois -- Chicago; TRUE CRIME / General; Murder; Murder -- Investigation; Trials (Murder); Illinois -- Chicago